PERANCANGAN SISTEM INFORMASI INSENTIF KINERJA PROMOTOR PT. CHANGHONG ELECTRIC INDONESIA - M. Septiawan; Alya Putri Rizaldy; Mardiani (PT. Hasba Edukasi Mandiri, 2026)
The development of information technology encourages organizations to implement digital transformation in various business processes to improve the efficiency and accuracy of data management. PT Changhong Electric Indonesia currently calculates Promoter Performance Incentives using Microsoft Excel, which potentially leads to calculation errors, data inconsistencies, and requires a relatively long time for processing information. This research aims to develop a web-based promoter incentive calculation information system that can enhance the accuracy, efficiency, and security of incentive data management. The method used in this research is Agile Software Development with the Scrum framework, consisting of product backlog, sprint planning, daily scrum, and sprint retrospective stages. System requirements analysis was conducted using the PIECES method to identify issues within the current system. The system was developed using the Laravel framework, PHP programming language, MySQL as the database, Tailwind CSS as the user interface framework, and jQuery to improve user interactivity. The results indicate that the developed system successfully automates the promoter incentive calculation process, reduces the risk of calculation errors due to manual processing, accelerates sales data recapitulation, and increases the transparency of incentive information for promoters. The novelty of this research lies in the integration of sales transaction management, promoter targets, incentive models, and commission calculations into a centralized, web-based system. The resulting system is expected to support the company's operational effectiveness and serve as a reference for the development of sales incentive systems in similar companies.